Analisis Pengujian Kualitas Air Sumur Bor, Air Galon R.O, dan Air PDAM Berdasarkan Pengukuran Ph, Kekeruhan (Turbidity), dan Total Dissolved Solids (TDS) - Rahmatullah, Azwar; Dwangga, Mierta; Nurbia, Nurbia; Yasin, Azalia Fajri (Jurnal Teknologi Lingkungan Lahan Basah, 2025)
Clean water that meets quality standards is crucial for public health, especially in urban areas that rely on various water sources such as drilled wells, reverse osmosis (RO) gallon water, and PDAM water. This study was conducted to analyze the quality of these three types of water based on three main parameters: pH, turbidity, and total dissolved solids (TDS). The study was conducted in April at the Environmental Engineering Laboratory of Muhammadiyah University of Sorong. Samples were taken from 15 locations, each for drilled well water, RO gallon water, and PDAM water. pH measurements were carried out using a digital pH meter and litmus paper, while turbidity and TDS were measured using the LH-Z10A Portable TSS & Turbidity Meter. The results showed that all water samples had turbidity and TDS values that were still within the safe threshold according to the Minister of Health Decree No. 2/2023, namely